(untitled) (Annual of the Faculty of Philosophy in Skopje, 2008)
The role o f the Great European powers in the process of creation of the modern Balkan states in the 19’h century was indisputable. However we can not neglect the reason for their interference in the region and the establishing o f the new states. Nonetheless the fact that European powers were not inclined to weaken Ottoman Empire with ceasing parts of its territory, the situation in the region induced them to interfere. Serbian uprisings at the beginning of 19"’ century were the first signs that some European powers would be induced or interested to intemene in the ottoman internal affairs. Although Serbian were the first who rised against Ottoman rule, the interest o f the Powers enabled Greeks to had first independent Christian state in 19,h century Balkan. The Bulgarian case was much interested. It is impossible to compare Bulgarian armed struggle against Ottoman rule with the Serbian and Greek uprisings. Bulgarian struggle was belated and very weak, but the Russian interest for Bulgarian lands was very strong. That was the main reason for creating modern Bulgarian State.